V19. Neural correlates of otolith stimulation: Results of an EEG study. Issue 8 (August 2015) - Ertl, M.; Moser, M.; Dieterich, M.
<x xml:space="preserve">Abstract</x> Introduction The otolith organs sense the head's translational motion and its orientation relative to gravity. Signals proportional to head acceleration are carried by otolith afferents from the vestibular endorgan to the brain. fMRI studies revealed the insula, the inferior parietal lobule as well as the superior/middle/transverse temporal gyri as regions involved in the processing of otolith input (Schlindwein et al., 2008). However, due to the poor temporal resolution of the BOLD signal knowledge on the temporal processing and the interaction between the distinct brain areas is sparse. Recent EEG studies using loud click sounds (McNerney et al., 2011; Todd et al., 2014) reported reliable evoked potentials observable on the scalp. Though, the used stimuli resulted in a superposition of auditory and vestibular signals. Aim of the current study was to avoid this superposition by the use of passive translational body movements for otolith stimulation. Methods The EEG of thirteen healthy, right-handed subjects was recorded while they were seated on a motion platform. Subjects were seated in a padded racing seat mounted on the platform. In order to mask motion related sounds by the platform subjects wear head phones by which white noise of 90 dB (SPL) was presented. During the experiment the platform performed translational movements along the interaural (IA) axis, the dorsoventral (DV) axis and the nasooccipital (NO) axis. The EEG was analyzed to visualize the potentials evoked by the onset of the movement. Results We identified a series of potentials evoked by this stimulation. In particular we found a positive component peaking about 40 ms after acceleration onset, a negative component after about 80 ms, followed by another positive component after approximately 200 ms (Fig. 1). Voltage maps showed strongest activity in electrodes over the parietal, occipital lobes and at electrode Cz (Fig. 2). Source localization estimated the inferior parietal lobe, the superior frontal gyrus, and the insula as potential generators of these components. Discussion These potentials are in line with the previously published EEG studies on otolith stimulation using loud click sounds. Additionally, the estimated generators nicely fit the locations reported in several previous imaging studies on the stimulation of the vestibular system. We conclude that recording EEG during passive body movements is a feasible way to shed some light on the temporal processing of vestibular otolith input and the interaction between the involved brain areas. Acknowledgements The work was supported by Deutsche Stiftung Neurologie, Graduate School for Systemic Neuroscience (GSN) and the German Federal Ministry of Education and Research (BMBF grant code 01 EO 0901).